The Anne Boleyn Illusion is a Six-Fingered Salute to Sensory Remapping - Roger Newport; Dominic Y. Wong; Ellen M. Howard; Eden Silver (i-Perception, 2016)
The Anne Boleyn Illusion exploits the somatotopic representation of touch to create the illusion of an extra digit and demonstrates the instantaneous remapping of relative touch location into body-based coordinates through visuo-tactile integration. Performed successfully on thousands, it is also a simple demonstration of the flexibility of body representations for use at public events, in schools or in the home and can be implemented anywhere by anyone with a mirror and some degree of bimanual coordination.